Penerapan Model-Model Manajemen Dalam Pengembangan Pondok Pesantren - Kadir, Abdul (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2024)
The aim of this research is to analyze the concept of management and development models for Islamic boarding schools, as well as the application of management models in the development of the Al-Munawwir Sangatta Selatan Islamic boarding school. This research uses a qualitative approach with a case study type. The research results show that the development of Islamic boarding schools is a process that involves various aspects to improve the quality of education in Islamic religious educational institutions (Islamic boarding schools). The application of management models in the development of Islamic boarding schools can increase the effectiveness and efficiency of Islamic religious education institutions, in this case the Al-Munawwir Sangatta Selatan Islamic Boarding School. Several relevant management models, including performance management models, change management models, risk management models, and operational management models, have been grouped, adopted, and applied into four models, namely: performance management models, change management models, risk management models, and operational management models. Thus, the Al-Munawwir Islamic boarding school has implemented management models in its development by adopting Agranoff and McGuire's integrative collaborative management model